Representation of beauty standards in social media: The analysis of hegemony concepts in cultural studies - Hadist, Afdalina Amalul (Maliki Interdisciplinary Journal, 2024)
Beauty is one of the critical aspects of human social life, which has long been a subject of discussion and thought. However, with the advancement of technology and the popularity of social media, the concept of beauty has undergone a radical transformation. This research attempts to explore how beauty standards in social media create a hegemony that influences people's views on beauty. The concept of hegemony, introduced by Antonio Gramsci's socio-political theory, is used as the analytical framework in this research. Through analyzing social media content, advertising campaigns, and relating them to the concept of hegemony, this research identifies various elements that contribute to the formation of hegemony in beauty standards.